2020
DOI: 10.1302/2046-3758.91.bjr-2019-0043.r2
|View full text |Cite
|
Sign up to set email alerts
|

Mechanotransduction in osteogenesis

Abstract: Bone is one of the most highly adaptive tissues in the body, possessing the capability to alter its morphology and function in response to stimuli in its surrounding environment. The ability of bone to sense and convert external mechanical stimuli into a biochemical response, which ultimately alters the phenotype and function of the cell, is described as mechanotransduction. This review aims to describe the fundamental physiology and biomechanisms that occur to induce osteogenic adaptation of a cell following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 100 publications
1
66
0
2
Order By: Relevance
“…Mechanotransduction is known to be important for the regulation of osteogenic differentiation of MSCs [ 53 ]; therefore, we took a closer look at the bone-related genes contributing to the overrepresented pathways shown in Figure 3 (GO:0071773, GO:0045669, GO:0031214, GO:0030282 and GO:0045778). Our analysis revealed 24 significantly upregulated genes ( Figure 5 A,B) with a log 2 -fold change higher than 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanotransduction is known to be important for the regulation of osteogenic differentiation of MSCs [ 53 ]; therefore, we took a closer look at the bone-related genes contributing to the overrepresented pathways shown in Figure 3 (GO:0071773, GO:0045669, GO:0031214, GO:0030282 and GO:0045778). Our analysis revealed 24 significantly upregulated genes ( Figure 5 A,B) with a log 2 -fold change higher than 2.…”
Section: Resultsmentioning
confidence: 99%
“…Commitment towards the osteogenic lineage in hMSCs can be achieved via mechanotransduction [ 53 ], applying various types of physical stimuli such as tension [ 67 ], compression [ 68 , 69 ] and fluid shear stress [ 70 ]. Although a variety of mechanosensors have been described for different bone cells, e.g., integrins and cadherins/β-catenin in osteoblasts [ 71 , 72 , 73 , 74 ], the aforementioned mechanoperception by the primary cilium is the key player in hMSCs [ 37 , 75 ], resulting in an extensive upregulation of the expression levels of PTGS2 and BMP2 .…”
Section: Discussionmentioning
confidence: 99%
“…The mechanosensitivity of cells determines a specific response to mechanical stimulation. Mechanical stretch can modulate several different cellular functions, such as the electrical activity of cardiac muscle [1], osteogenesis [2], and the myogenic response of small arteries [3]. Although mechanosensitivity is essential to all cells, studies were mainly devoted to clarify signal mechanotransduction in those cells that play a fundamentally mechanical role.…”
Section: Introductionmentioning
confidence: 99%
“…Developmental consequences could occur due to cells sensing and reacting to their physical environment through mechanotransduction, which is the cellular process of translating mechanical forces into biochemical signals or into the activation of diverse signalling pathways [ 42 ], or through the differential reaction of specific cell types to a genetic variant. Studies of mechanotransduction have shown that many diseases result from modifications in the force transmissions among cellular components and tissues that can be traced to changes in extra cellular matrix mechanics, cytoskeleton dynamics, the mechanosensing process of the cell, or altered downstream signaling pathways [ 42 , 43 ]. In the case of PR, defects in mechanotransduction of the involved tissues could underlie one or all of the defects, or the genetic variants currently associated with PR-like diseases could be functionally related through a shared genetic network.…”
Section: Uncertainty Of Diagnosismentioning
confidence: 99%